Medicines optimisation in East Sussex care homes. Issue 5 (17th May 2019) - Blythin, Kayt; Harries, Elizabeth
Abstract : Clinical pharmacists now have an important role in medicines optimisation within the care home setting. In this article, the authors discuss their approach to medication reviews and medicines optimisation in care homes in East Sussex.